Zn-M-CO3 Layered Double Hydroxides (M=Fe, Cr, or Al): Synthesis, Characterization, and Removal of Aqueous Indigo Carmine - Salima Bouteraa; Fatiha Boukraa Djelllal Saiah; Sarah Hamouda; Nourredine Bettahar (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
In this approach, Zn-M+3 layered double hydroxides (LDHs) with M+3 = Fe, Cr, or Al were synthesized by the co-precipitation method from the aqueous solution at a constant solution pH. The as-synthesized samples were characterized by XRD analysis, FTIR spectra, BET techniques and simultaneous thermogravimetric-differential scanning calorimetry (TGA/DSC). XRD analysis showed that Zn-Fe-CO3 had the greatest lattices parameters. BET surface area of Zn-Fe-CO3 was calculated as 52.24 m2.g-1 and was higher than Zn-Cr-CO3 and Zn-Al-CO3 with 46.70 and 49.99 m2.g-1, respectively. The FTIR spectra clearly confirmed the presence of carbonate anions in the structure of the LDHs. Adsorption experiments for Indigo Carmine (IC), as the main model organic pollutant in this study from aqueous solution onto synthetized samples were carried out in terms of solution pH, contact time and initial dye concentration. Experimental results indicate that the capacity of dye uptake augmented rapidly within the first 15, 40, and 55 minuts for Zn-Fe-CO3, Zn-Cr-CO3 and Zn-Al-CO3 respectively and then stayed practically the same regardless of the concentration. Adsorption kinetics studies revealed that the adsorption process followed pseudo-second order kinetics model instead of a pseudo-first-order model. The adsorption isotherm data follow the Langmuir equation in which parameters are calculated. The maximum Langmuir monolayer adsorption capacities were 94.87, 21.79, and 66.71 mg.g-1, respectively, for Zn-Fe-CO3, Zn-Cr-CO3, and Zn-Al-CO3. The adsorption capacities were slightly influenced by the pH variations from 5 to 10, showing the advantage of using these materials in water treatments in a wide pH range. Finally, the IC removal is proven by the presence of IC functional groups in IR spectra and thermograms. TGA/DSC of Zn-Fe-CO3 obtained after removal of IC indicate that the LDHs stabilizes IC and delays the combustion of adsorbed molecules. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).